Thinking Simón Rodríguez from artistic practices: indiscipline as an affective resistance - Cerrillo, Rubén (2021)
This paper seeks to develop a sentimental account of what it has implied for the Mitote ICDAC to review the thought of Simón Rodríguez from two fundamental points. First from his postulates about Popular Education, which was openly decolonial at the time of the Colony and much earlier that the term was coined as a philosophical matrix, which serves as a root and fertile ground to re-think the dimensions of what it means to act from the Public University, and articulate it as a possible space to act from an undisciplined paradigm in the face of the hegemony of knowledge. Second, think about it from artistic practices as a way of exercising situated self-narration, as a means that empowers us to ask/think the questions that cross us as a way of being in the world and with it to be able to think about it in our own terms, what it is one of the fundamental invitations in Rodríguez’s work.